A Lightweight Post-Quantum Lattice-Based RSA for Secure Communications - Mustafa, Iqra; Khan, Imranullah; Aslam, Sheraz; Sajid, Ahthasham; Mohsin, Syed Muhammad; Awais, Muhammad; Qureshi, Muhammad Bilal (My University, 2020)
Conventional RSA algorithm, being a basis for several proposed cryptosystems, has remarkable security laps with respect to confidentiality and integrity over the internet which can be compromised by state-of-the-art attacks, especially, for different types of data generation, transmission, and analysis by IoT applications. This security threat hindrance is considered to be a hard problem to solve on classical computers. However, bringing quantum mechanics into account, the concept no longer holds true. So, this calls out for the modification of the conventional pre-quantum RSA algorithm into a secure post-quantum cryptographic-based RSA technique. In this research, we propose a post-quantum lattice-based RSA (LB-RSA) for IoT-based cloud applications to secure the shared data and information. The proposed work is validated by implementing it in 60-dimensions. The key size is about .152\times 10^{5}$ -bits and generation time is 0.8 hours. Furthermore, it has been tested with AVISPA, which confirms security in the presence of an intruder. Moreover, the proposed LB-RSA technique is compared with the existing state-of-the-art techniques. The empirical results advocate that the proposed lattice-based variant is not only safe but beats counterparts in terms of secured data sharing.
Keywords: Gauss-sieve algorithm; IoT application; Lattice-based cryptography; LB-RSA; Post-quantum cryptography